Implementation of the Independent Learning Curriculum in Improving Students' Creative Thinking Skills in PAI Lessons at SMKN 10 Bandung - Taupik Hamdani; Rifki Ulfiansyah CH; Nur Ainiyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
This research is motivated by the low level of students' creative thinking skills, the existence of an independent learning curriculum that can encourage students' creative thinking skills in PAI subjects. The purpose of this study was to determine the Implementation of the Independent Learning Curriculum in Improving Students' Creative Thinking Ability in PAI subjects. This study uses a qualitative method with a descriptive approach. The researcher uses triangulation on data collection technique. The data analysis technique is through data collection, data reduction and data presentation and conclusions. The results and conclusions of this study are that the implementation of an independent learning curriculum which is carried out using differentiated learning and assessment implementation patterns so that it can improve students' creative thinking skills in PAI lessons which classified into very good category on both fluent thinking, flexible thinking or original thinking, whereas the good category thinking ability indicator are those student’s ability in elaboration.